The Role Of IT Governance In Enhancing Information Security - كراز شادي (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The study aimed to determine the impact of the dimensions of information technology governance represented by (planning and organizing, acquisition and implementation, support and delivery, follow-up and evaluation) in enhancing information security in the banks listed on the Damascus Stock Exchange, the analytical descriptive approach was relied upon, and the study community included private banks The Syrian company is listed on the Damascus Stock Exchange numbering fourteen banks, 100 questionnaires were distributed to workers in the financial section in the banks of the study sample and 85 questionnaires were analyzed through the spss statistical program and the results were extracted. The study found that there is a significant effect of the dimensions of information technology governance represented by (planning and organizing, acquisition and implementation, support and delivery, follow-up and evaluation) in enhancing information security in the banks listed on the Damascus Stock Exchange, and the study recommended that all banks should commit to applying a model to measure Information technology governance according to the Copt framework to be a standard measure of the level of information technology governance and an assistant to these banks to know their current status.